Hubungan Pengetahuan tentang Covid-19 dengan Kepatuhan Physical Distancing di Tarakan - Hafandi, Zul; Ariyanti, Ririn (Sekolah Tinggi Ilmu Kesehatan Mutiara Mahakam, 2020)
Coronavirus 2019 (Covid-19) is a disease that is pandemic almost all over the world. Covid-19 infection can cause mild, moderate or severe symptoms. Covid-19 can be transmitted from humans through close contact and droplets, not through the air. WHO recommends physical distancing to prevent the spread of Covid-19. The purpose of this study was to relationship of knowledge about Covid-19 with obedience physical distancing. This research is a descriptive correlative study with cross sectional approach, the sampling technique used accidental sampling , the data is obtained from the Google form filled out by the researcher. The results of this study showed p-value 0,000 <Î± 0.05 so that there is a significant relationship between knowledge about Covid-19 with obedience physical distancing